SOME ASPECTS OF PRAWN CULTURE IN THE SEASONAL AND PERENNIAL FIELDS OF VYPEEN ISLAND - George, K V (Indian Journal of Fisheries, 2011)
Prawn culture is extensively practised in the paddy fields (seasonal fields) and other low lying areas (perennial fields) of Vypeen Island. Though the seasonal fields are found to be more productive, the perennial fields, which are available for prawn culture throughout the year, are not less important. Prawns stay for longer time and attains larger size in this type of fields. The average annual production of prawns is 903.3 and 838.6 kg|ha in the seasonal and perennial fields respectively. The month-wise catch rates show that higher catch rate is generally observed in January-iMarch period. Four species of penaeid prawns, Metapenaeus dobsoni, M. monoceros, Penaeus indicus and P. monodon constitute the culture fishery of which M. dobsoni contributes more than 50% of the catch. It is observed that M. dobsoni in the perennial fields grow at an average rate of 10.0 mm per month. Although, the total expenditure to run the seasonal field is higher than that of the perennial fields, the net income realised from the seasonal field is always found to be better. It is therefore concluded that the paddy field prawn culture is more profitable than the culture of prawns in perennial fields.